Hipertrofia do ventrículo esquerdo e perfil restritivo pulmonar no paciente com anemia falciforme - Menezes Neto, Osvaldo Alves de (2014)
Sickle cell anemia (SCA) is the result of a mutation in the beta globin chain gene, resulting in the production of an abnormal hemoglobin, Hb S. Losing oxygen, Hb S decreases its solubility, suffering aggregation and polymerization, which hardens and distorts the erythrocytes causing occlusion of small blood vessels. The venocclusive phenomena characteristic of AF may occur in any organ, including the heart and lung. These complications are among the leading causes of morbidity and mortality related to this disease. Objectives: To evaluate cardiopulmonary involvement of children, adolescents and young adults with sickle cell anemia and investigate the correlations between left ventricular hypertrophy (LVH) and restrictive lung pattern variables, as well as any associations. Method: Cross-sectional study in which were consecutively included patients with SCA, attending the Pediatric Hematology, University Hospital, Federal University of Sergipe. Demographic, clinical and laboratory data have been collected and ecocadiograma and spirometry were performed. Results: 153 patients have been studied, with a mean age of 14.9 years. LVH was identified in 40% of patients, without systolic or diastolic dysfunction. Patients with LVH had lower hemoglobin levels, higher albumin/creatinine ratio and AST (p=0.03, 0.02 and 0.03 respectively). Impairment in pulmonary function has been found in 60.9 % of patients, of which 46.9% had pulmonary restrictive pattern. These had higher mean of age (p=0.04) and showed higher mean corpuscular volume, AST and creatinine clearance (p=0.03, 0.03 and 0.02, respectively). There was not statistic between LVH and restrictive lung pattern (p=0.49). suggesting that they are events with different natural histories. The findings of the study indicate the need for investigation of cardiopulmonary alterations in patients with sickle cell anemia. Spirometry and echocardiography should be performed independently.